2017
DOI: 10.1186/s12934-017-0681-1
|View full text |Cite
|
Sign up to set email alerts
|

Large scale validation of an efficient CRISPR/Cas-based multi gene editing protocol in Escherichia coli

Abstract: BackgroundThe exploitation of the CRISPR/Cas9 machinery coupled to lambda (λ) recombinase-mediated homologous recombination (recombineering) is becoming the method of choice for genome editing in E. coli. First proposed by Jiang and co-workers, the strategy has been subsequently fine-tuned by several authors who demonstrated, by using few selected loci, that the efficiency of mutagenesis (number of mutant colonies over total number of colonies analyzed) can be extremely high (up to 100%). However, from publish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(91 citation statements)
references
References 35 publications
(64 reference statements)
0
91
0
Order By: Relevance
“…Our results show that this sequence was easily engineered using the Cas12a-encoding plasmids designed by Yan et al (29). These plasmids are easy to use and allow multiple rounds of mutagenesis similar to previously reported Cas9 approaches (6). Cas12a also brings the advantage that it processes its own crRNAs, which we think will allow certain flexibility in the future when dealing with organisms with poorly characterised promoter sequences.…”
Section: Observation Of a Fima Terminator Mutant By Afmmentioning
confidence: 92%
See 2 more Smart Citations
“…Our results show that this sequence was easily engineered using the Cas12a-encoding plasmids designed by Yan et al (29). These plasmids are easy to use and allow multiple rounds of mutagenesis similar to previously reported Cas9 approaches (6). Cas12a also brings the advantage that it processes its own crRNAs, which we think will allow certain flexibility in the future when dealing with organisms with poorly characterised promoter sequences.…”
Section: Observation Of a Fima Terminator Mutant By Afmmentioning
confidence: 92%
“…The efficiency of genome engineering strains has been shown to depend on the efficiencies of gRNAs to direct Cas9 DNA cleavage and donor oligos (6). Using the same crRNA (crRNA1) to generate several mutations at the same target sequence we saw that each mutation was produced with efficiencies ranging from 10% to 100%.…”
Section: Observation Of a Fima Terminator Mutant By Afmmentioning
confidence: 99%
See 1 more Smart Citation
“…Gomaa et al reported that recombination events had occurred between direct repeats of the artificial CRISPR‐array on the plasmid, losing the genome targeting spacer sequences. Other studies also found similar recombination‐induced spacer loss in the CRISPR array on plasmids . Moreover, under the genome‐targeting stress, the mutation or deletion that disrupts the cas genes would also allow the bacteria to survive .…”
Section: Dna Cleavage By Cas9 and Cas12amentioning
confidence: 73%
“…The nuclease aided methods make use of DNA cleaving enzymes such as the meganuclease I-SceI (Kuhlman & Cox, 2010) or the endonuclease Cas9 in CRISPR set-ups (Li et al, 2015;Ng, Hung, Kao, Zhou, & Zhang, 2016;Zerbini et al, 2017;Zhao et al, 2016), which both induce a lethal double-stranded break at the place of recognition. Repair is done by recombination with an introduced DNA fragment using the same λ-Red genes.…”
mentioning
confidence: 99%